Pengaruh Gaya Hidup Terhadap Kondisi Keuangan Pribadi pada Generasi Z - Mutia Sirwaty; Wa Ode Rayyani (Jurnal Ekonomi dan Bisnis Digital, 2025)
This study aims to analyze the influence of lifestyle on the personal financial conditions of Generation Z, individuals born between 1997 and 2012. The research employs a quantitative method by distributing questionnaires to 34 respondents aged 18–27 years, and the data are analyzed using simple linear regression. The results indicate that lifestyle has a significant effect on personal financial conditions, as demonstrated by the t-calculated value (3.047) > t-table (2.037) and a significance level of 0.005 < 0.05. The higher the level of a consumptive lifestyle, the greater the likelihood of disturbances in personal financial conditions. These findings emphasize the importance of financial literacy education to help Generation Z manage their finances wisely.